NUTRIENT UPTAKE AND BIOLOGICAL NITROGEN FIXATION IN COWPEA UNDER BIOCHAR-PHOSPHORUS INTERACTION - P. D. Hiama; N. Ewusi-Mensah; V. Logah (Journal of Animal and Plant Sciences, 2019)
Research exploiting biochar-phosphorus interactions on biological nitrogen fixation (BNF) and nutrient uptake in legumes is very scarce. This paper reports the short-term effect of rice husk biochar and phosphorus application on nutrient uptake, nodulation and nitrogen fixation of cowpea in both pot and field experiments in the semi-deciduous forest zone of Ghana. Phosphorus fertilizer (triple superphosphate (TSP)) was applied at 0, 30 and 60 kg ha-1designated respectively as P0, P30 and P60 while biochar was applied at 0, 2.5, 5 and 7.5 t ha-1 designated respectively as B0, B2.5, B5 and B7.5. Interaction between biochar and phosphorus increased nodule dry weight, number of nodules per plant and fixed nitrogen more than the sole applications. The highest number of nodules plant-1 and nodule dry weight were observed under P30B5. The highest N fixed (36.15 kg ha-1) was observed under P60B5 emphasizing the role of phosphorus in BNF. Increasing biochar beyond 5.0 tha-1 decreased BNF. Nitrogen, phosphorus and potassium uptake were significantly (p≤ 0.05) improved following biochar and TSP applications under both greenhouse and field conditions. The highest N uptake of 30.79 kg ha-1was observed under P30B5 amended plots while P60B7.5 plots produced the highest P and K uptake. Overall, the results indicate good prospect of exploiting biochar-phosphorus interactions to enhance BNF and productivity of legumes in tropical climate.
Keywords: Biochar; cowpea; nodulation; plant nutrients; triple superphosphate